2014
DOI: 10.3727/108354214x13927625340235
|View full text |Cite
|
Sign up to set email alerts
|

Including Pets When Undertaking Tourism Activities: Incorporating Pet Attachment into the TPB Model

Abstract: As modern individuals place increasing value on tourism and have an increasing attachment to their pets, it is important for scholars, practitioners, and other relevant parties to determine whether pet owners will plan to have their pets accompany them when travelling for tourism purposes. Based on an analysis of 458 dog owners, this study's results provide support for the application of the TPB model in the context of this subject. The findings of this study on the influence of pet attachment on owners' attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 63 publications
1
12
0
2
Order By: Relevance
“…Many researchers find that safety and comfort of the pets is the main issue the owners are dealing with, while planning trips or travelling with their pets (Leggat & Speare, 2000;Kirillova, Lee & Lehto, 2015;Peng, Chen & Hung, 2014). Desire to travel with pets is strong, but actual rates of travelling with pets might be comparatively low due to the insufficiency of pet-friendly accommodations (Carr & Cohen, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers find that safety and comfort of the pets is the main issue the owners are dealing with, while planning trips or travelling with their pets (Leggat & Speare, 2000;Kirillova, Lee & Lehto, 2015;Peng, Chen & Hung, 2014). Desire to travel with pets is strong, but actual rates of travelling with pets might be comparatively low due to the insufficiency of pet-friendly accommodations (Carr & Cohen, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Hung et al (2012) identified six beliefs or actions that characterise the relationship between a dog and its human owners: firstly, having a dog helps improve the owners’ physical and mental health; secondly, dog owners feel the family is complete without a dog; thirdly, families usually bring a dog when visiting friends and/or family members; fourthly, dog owners believe that dogs should have the same rights and privileges as family members; fifthly, most owners have a photo of their dog in their house and/or office; and sixthly, dog owners believe that pets are more loyal than a lot of people. This relationship, thus, has an important influence on the planning and consumption of tourist products and the behaviour of dog owners in terms of travel (Peng et al , 2014): the stronger the emotional attachment, the more pet owners would be willing to pay for holidays that accommodate their pet (Kirillova et al , 2015). It is, therefore, necessary to analyse how destinations have adapted to the relationship between owners and their pets (Peng et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This relationship, thus, has an important influence on the planning and consumption of tourist products and the behaviour of dog owners in terms of travel (Peng et al , 2014): the stronger the emotional attachment, the more pet owners would be willing to pay for holidays that accommodate their pet (Kirillova et al , 2015). It is, therefore, necessary to analyse how destinations have adapted to the relationship between owners and their pets (Peng et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations